Drug-Related Problems of Patients in Primary Health Care Institutions: A Systematic Review - Ni, Xiao-Feng; Yang, Chun-Song; Bai, Yu-Mei; Hu, Zi-Xian; Zhang, Ling-Li (Frontiers in Pharmacology, 2021)
Introduction: Drug-related problems (DRPs) are not only detrimental to patients’ physical health and quality of life, but also lead to a serious waste of health care resources. The condition of DRPs might be more severe for patients in primary health care institutions. Objective: This systematic review aimed to comprehensively review the characteristics of DRPs for patients in primary health care institutions, which might be helpful to find effective strategies to identify, prevent and intervene with DRPs in the future. Methods: We searched three English databases (EMbase, The Cochrane library, PubMed) and four Chinese databases (CNKI, CBM, VIP, Wanfang). Two of researchers independently conducted literature screening, quality evaluation and data extraction. Qualitative and quantitative methods were combined to analyse the data. Results: From 3368 articles screened, 27 met the inclusion criteria and were included in this review. The median (inter-quartile range, IQR) of the incidences of DRPs was 70.04%(59%), and the median (IQR) of the average numbers of DRPs per patient was 3.4(2.8). The most common type of DRPs was “treatment safety”. The causes of DRPs were mainly in the prescribing section including “drug selection” and “dose selection”, while patients’ poor adherence in the use section was also an important cause of DRPs. Risk factors such as the number of medicines, age and disease condition were positively associated with the occurrence of DRPs. In addition, the medians (IQR) of the rate of accepted interventions, implemented interventions and solved DRPs were 78.8% (22.3%), 64.15% (16.85%) and 76.99% (26.09%), respectively. Conclusion: This systematic review showed the condition of DRPs in primary health care institutions was serious. In pharmaceutical practice, the patients with risk factors of DRPs should be monitored more closely. Pharmacists could play important roles in the identification and intervention of DRPs, and more effective intervention strategies need to be established in the future.